Kebijakan Pendirian Universitas Islam Internasional Indonesia: (Analisis Esensi dan Wacana Internasionalisasi Pendidikan Islam Indonesia) - Ambarwati Ambarwati; Samsul Ma’arif (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2022)
The Indonesian International Islamic University (UIII) which was established based on Presidential Regulation Number 57 of 2016 has 3 (three) pillars, namely Islamic values, insights, and global projections, as well as Indonesian national character. The policy is that UIII organizes master and doctoral programs in the field of study of Islamic religion, social sciences and humanities as well as science and technology in accordance with statutory provisions, is a tertiary institution with a legal entity and has Academic Freedom, Freedom of Academic Opinion and Scientific Autonomy. Its role in internationalization is to become a Center for Strategic Assessment), to become one of the leading academic institutions in studies related to Islam and the Muslim community in the world, and to provide a stimulus for campuses in Indonesia to think more internationally.